2015
DOI: 10.5812/atr.22602
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of the Relative Impact of Obesity on Hemodynamic Stability During Acute Hemorrhagic Shock

Abstract: Background:Evidence suggests that morbid obesity may be an independent risk factor for adverse outcomes in patients with traumatic injuries.Objectives:In this study, a theoretic analysis using a derivation of the Guyton model of cardiovascular physiology examines the expected impact of obesity on hemodynamic changes in Mean Arterial Pressure (MAP) and Cardiac Output (CO) during Hemorrhagic Shock (HS).Patients and Methods:Computer simulation studies were used to predict the relative impact of increasing Body Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Obesity is one of the major risk factors for DVT [20]. Several reports have shown that venous return in the inferior vena cava or in the femoral vein is reduced in obese patients due to obesity-induced increases in intra-abdominal pressure [21, 22]. Our results were comparable with the results on venous flow of the lower extremities in these reports.…”
Section: Discussionsupporting
confidence: 89%
“…Obesity is one of the major risk factors for DVT [20]. Several reports have shown that venous return in the inferior vena cava or in the femoral vein is reduced in obese patients due to obesity-induced increases in intra-abdominal pressure [21, 22]. Our results were comparable with the results on venous flow of the lower extremities in these reports.…”
Section: Discussionsupporting
confidence: 89%
“…The Sterling-Summers model extended the Guyton model to explore the effects of morbid obesity on MAP and CO during hemorrhage (Sterling, Jones, Coleman, & Summers, 2015). Body mass Index (BMI) was used to quantify obesity, parameter values were tuned from known population distributions, and percent changes in hemodynamic quantities were calculated and compared with nonobese patients.…”
Section: Global Hemodynamics During Traumamentioning
confidence: 99%
“…To date, mathematical models of hemorrhage generally have relied on GH formalisms coupled with a prescribed bleeding rate (18,29,33,36). The Reisner-Heldt model simulated hemorrhage by connecting a resistive pathway to atmospheric pressure and tuning the resistance to match blood volume loss to experimental data (33).…”
Section: Introductionmentioning
confidence: 99%